1992
DOI: 10.1101/gad.6.12a.2248
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic lethality in mice homozygous for a targeted disruption of the N-myc gene.

Abstract: The N-myc gene encodes a putative transcription factor that is thought to function in the regulation of gene expression during cell differentiation and/or growth. To examine the role of N-myc during development, we have used targeted mutagenesis in embryonic stem cells to produce a mouse line that carries an N-myc null allele. Mice homozygous for the mutation died between 10.5 and 12.5 days of gestation. Histological analysis of mutant embryos revealed that organs and tissues expected at these stages of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(217 citation statements)
references
References 40 publications
5
211
1
Order By: Relevance
“…N-myc knockout mice had been generated concomitantly by three independent groups. [11][12][13] Embryonic lethality was consistently observed between embryonic days E10.5 and E12.5 of gestation, with developmental delay and small size of mesonephros, lung, heart, and gut. Interestingly, mutant mice with 25% of wild-type levels of N-myc protein die at birth and are unable to breathe because of a severe deficiency in lung-branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…N-myc knockout mice had been generated concomitantly by three independent groups. [11][12][13] Embryonic lethality was consistently observed between embryonic days E10.5 and E12.5 of gestation, with developmental delay and small size of mesonephros, lung, heart, and gut. Interestingly, mutant mice with 25% of wild-type levels of N-myc protein die at birth and are unable to breathe because of a severe deficiency in lung-branching morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Myc was shown to be necessary for traverse into S phase of the cell cycle (Heikkila et al, 1987), a finding recently underscored by the conditional knockout of c-Myc (de Alboran et al, 2001;Trumpp et al, 2001). Thus, not surprisingly, both c-Myc and N-Myc are essential for vertebrate development (Stanton et al, 1990;Sawai et al, 1991;Charron et al, 1992;Moens et al, 1992;Davis et al, 1993). In addition, numerous studies showed that Myc activation was sufficient to provoke diverse cancers (Adams et al, 1985;Leder et al, 1986) and, more recently, that Myc is continuously required to maintain the transformed state (Felsher and Bishop, 1999;Pelengaris et al, 1999;Jain et al, 2002).…”
Section: The Myc Paradoxmentioning
confidence: 99%
“…N-myc drives proliferation of granule neuron precursors derived from neuronal progenitor cells of the developing forebrain and hindbrain (10). Constitutive deletion of N-myc is embryonic lethal (6,9), whereas conditional inactivation in neuronal progenitor cells leads to ataxia, behavioral abnormalities, and tremors that correlate with an overall 2-fold decrease in brain mass that disproportionately affects the cerebellum and the cerebral cortex, both of which show signs of disorganization. There exists severely compromised proliferation at the cellular level, including striking decrease in S phase and mitotic cells, whereas apoptosis is unaffected.…”
Section: N-myc In Normal Developmentmentioning
confidence: 99%
“…For instance, mouse embryonic stem cells (ESC) homozygous for deletion of either C-myc or N-myc genes display morphology without aberrant proliferation or differentiation compared with wildtype ESCs (6,7) and N-myc can functionally replace C-myc in murine development (8). However, regional morphology of the central nervous system differs in N-myc-null embryos from wild-type embryos, despite upregulation of C-myc (9).…”
Section: N-myc In Normal Developmentmentioning
confidence: 99%